Effects of Moringa oleifera aqueous seed extracts on reproductive traits of heat-stressed New Zealand white female rabbits - Mutwedu, Valence B.; Nyongesa, Albert W.; Kitaa, Jafred M.; Ayagirwe, Rodrigue B. B.; Baharanyi, Chasinga; Mbaria, James M. (Frontiers in Veterinary Science, 2022)
Heat stress is reported to have deleterious effects on rabbit physiology by impairing reproductive performances arising from free radical production due to oxidative stress. Plant extracts have been listed among efficient and healthy strategies for alleviating the effects of free radicals in the body of an animal. Numerous studies have documented the medicinal value of Moringa oleifera on various body functional systems although most of these data have not been scientifically validated. The growing concern of heat stress owing to the effects of global warming has affected animal productivity and even reproductive health, yet mitigation measures are still scanty. To this end, we investigated the efficacy of Moringa oleifera aqueous seed extract on selected in the alleviation of morphofunctional impairments on functional systems of the body. Here, we quantified the effects of Moringa oleifera seed extracts on reproductive performances, hormonal profile, and ovarian histology in the management of heat stress in female rabbits. We were particularly interested in testing the hypothesis that Moringa oleifera seed extracts do not have medicinal value in the mitigation of oxidative stress accompanying heat-stressed animals and, therefore, affecting growth performance and reproductive value. Twenty-eight female rabbits aged 6 months and weighing between 2015.6 and 2322.7 g were randomly assigned to four treatment groups of temperature, relative humidity, temperature humidity index, and M. oleifera seed extracts as follows: T0: ambient temperature (18–24°C), 59 ± 0.48%, 23.6 ± 1.52; T1, T2, and T3: 35–36°C, 64 ± 0.6%, 32.5 ± 0.7, followed by 100, 200, and 0 mg/kg b.w of M. oleifera seed extracts. Artificial heat was introduced in each rabbit cage from 08:00 h to 16:00 h. Reproductive performances related to female rabbits and relevant biodata of their young ones were recorded. All animals were sacrificed at the end of 80 days of experiments, and blood was collected for hormonal assays and ovary tissues for histology. Data on hormones and reproductive parameters of adult females as well as parameters related to kid performance and milk yield were subjected to one-way ANOVA, and significant differences among treatment subjects were analyzed using Tukey's post-hoc test at 5% significance level. The results revealed a significant decrease (P < 0.05) in food consumption, body weight, and body weight gain in pregnant and lactating female rabbits exposed to heat stress. A decrease in fur removal by mothers, litter size from birth to weaning, litter weight, kid body weight, and body weight gain in adult rabbits submitted to heat stress was observed. The findings were also reflected on weekly milk yield and daily milk efficiency as well as serum hormone levels. Following administration of M. oleifera seed extracts at 200 mg/kg b.w., there was significant increase (P < 0.05) in these parameters. On the contrary, an increase (P < 0.05) in the number of services per conception, milk intake, and serum progesterone level was initially observed in the same subjects, but upon administration of M. oleifera seed extracts, there was a significant decrease (P < 0.05) on these measures. Ovarian histology of animals at T0 and T2 treatments showed structural features comparable to those of controls. Overall, our results show that administration of M. oleifera seed extracts at 200 mg/kg b.w possesses therapeutic value to the effects of oxidative stress associated with heat stress. Further pharmacological evaluation on seed extracts of M. oleifera may yield the much-needed medicine in the treatment and management of poor animal productivity and reproductive health arising from severe weather associated with global warming.